PERAN DEWAN KEAMANAN PERSERIKATAN BANGSA BANGSA DALAM PEMBATASAN PENGGUNAAN SENJATA - Amelia Agustin Tansia, Grace; Putrawan, Suatra (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015, 2015)
This paper aims to discuss how the UN Security Council's role in the restriction of the use of weapons. This paper is a normative legal research that uses statutory and case approaches. This paper will describe both the function and role of the UN Security Council as well as restrictions on the use of weapons for war. The conclusion of this research is that UN Security Council’s role in enforcing peace for countries, especially those engaged in war as well as in the use of weapons in war to keep attention to the humanity values as set out in customary international humanitarian law and the Hague Convention IV of 1907 by issuing resolution.
Keywords: United Nations, Security Council, Use of Weapons, War